Javelin: cueing postural alignment, and sprint mechanics within the approach - Maynard, M.
The establishment and maintenance of proper postural alignment form the basis for balance and control of the Center of Mass (CM) throughout preliminary approach, crossovers, and delivery phases of the javelin throw. The desired posture is an erect and vertical spine, with hips in a neutral position under the athlete. To aid in the hyper-extension and opening of the throwing shoulder in preparation for the delivery the chest should be elevated. The head should remain neutral in relation to the spine, except for being turned slightly in the direction of the throw. The athlete should attempt to run, and throw within this posture. It is necessary to execute an efficient running technique with the javelin to maintain proper postural alignment. Failure to control the postural alignment and CM during the run will result in an ineffective technical performance. There is a close relationship between postural alignment, and running mechanics utilized during the crossovers of the javelin approach. When possible efficient sprint technique should be enforced within the crossovers. It is common for javelin throwers to exhibit poor sprinting mechanics. Adduction and abduction of the legs during crossovers force a modification of proper sprint mechanics. However, this is not a license for the total abandonment of correct sprint mechanics. Time must be allocated for the teaching, drilling, and refining the athletes understanding of proper sprint mechanics. If the throwing coach is unfamiliar with sprint mechanic teaching progressions and exercises, they should utilize an available and knowledgeable sprints/ hurdles coach.